(untitled) (Materiali di Estetica. Terza serie, 2023)
The so-called Egyptian Blue is a peculiar shade of synthetic blue and in ancient Egypt it is used above all in funerary texts that accompany the deads, protecting them simbolically in the difficult access to the afterlife. Its presence is also attested in Mediterranean area until late antiquity, then it disappears in the Middle Ages and it finally re-emerges in the Renaissance, mainly in Raphael’s Triumph of Galatea. Perhaps this “survival” is not accidental: the Neoplatonic climate of the time conceives hieroglyphics as visible symbols of invisible ideas.